Internet Regulation as Governance of Privacy - Dias, Patricia Yurie (Law, State and Telecommunications Review, 2017)
Purpose ”“ Analysis of the elements of responsive regulation as mechanism used by companies as a governance of the right to privacy on the internet. Methodology/approach/design ”“ Study of the responsive regulation theory of Ayres and Braithwaite and the rules and laws related to the right to privacy on the internet. In addition, a legal case and regulations of the United States and European Union will be addressed. Findings ”“ Self-regulation, dialogue, collaboration and accountability of responsive regulation can contribute to the edition of minimum standards to be followed by companies or regulated as a governance of privacy on the internet.